1982
DOI: 10.1161/01.cir.66.4.881
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a shared mechanism of vasoconstriction in pulmonary and systemic circulation in hypertension: a possible role of intracellular calcium.

Abstract: SUMMARY We investigated the hemodynamics of the greater and lesser circulation in 35 patients with primary hypertension, as well as the effects of calcium-channel blockade, to test whether a common factor may account for the excessive vascular resistance in the two circuits and whether intracellular calcium concentration ([Ca++]i) may be involved. We proved that (1) elevated pulmonary arteriolar resistance (PAR) is not related to pulmonary blood flow and volume, pleural pressure, arterial oxygen or carbon diox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…In this study, the altered response to leptin was attributed to the pulmonary endothelial dysfunction present in SHR [10]. However, already in 1989, Guazzi and associates demonstrated that, in hypertension, the pulmonary and systemic circulations shared joint mechanisms of vasoconstriction directly related to increased calcium in vascular smooth muscle cells [11]. Cytosolic calcium concentration is directly coupled to smooth muscle contraction.…”
Section: Introductionmentioning
confidence: 93%
“…In this study, the altered response to leptin was attributed to the pulmonary endothelial dysfunction present in SHR [10]. However, already in 1989, Guazzi and associates demonstrated that, in hypertension, the pulmonary and systemic circulations shared joint mechanisms of vasoconstriction directly related to increased calcium in vascular smooth muscle cells [11]. Cytosolic calcium concentration is directly coupled to smooth muscle contraction.…”
Section: Introductionmentioning
confidence: 93%
“…The causes of this abnormal vasomotion have not been elucidated, and no convincing explanation has been derived from the analysis of the mechanisms that are commonly indicated as interfering with the pulmonary vasomotility in humans, 14 such as changes in the respiratory gases and pH of the blood, pleural pressure, blood volume and flow through the lungs, or in the function of the left side of the heart and the related backward influences. These reasons, and the positive correlation existing between systemic and pulmonary vascular resistance, have suggested that a common factor responsible for vasoconstriction may be at work in the pulmonary and systemic circulation in hypertension.…”
mentioning
confidence: 99%
“…Indeed, healthy aortic endothelium negatively regulates α1-agonists- and endothelin-1-induced contraction through a basal endothelial NO release [33-35], which is partly lost in spontaneously hypertensive rats [36-38]. The imbalance between NO and endothelin-1 signaling pathways may, at least, partially mediate pulmonary endothelial dysfunction in this hypertensive strain, together with previously described altered calcium handling [2]. Even if we found some similar pathobiological anomalies within the pulmonary circulation of SHR compared to those observed in PAH patients, there is no clear evidence that these two conditions share common early pathogenic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Guazzi et al hypothesized that this would be related to shared abnormal smooth muscle calcium handling mechanisms in the systemic and pulmonary resistive vessels [2]. In support of this notion, these authors reported an enhanced pulmonary vascular reactivity to hypoxia in patients with uncomplicated systemic hypertension [3].…”
Section: Introductionmentioning
confidence: 99%